2015
DOI: 10.1007/s00520-015-2708-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential factors associated with perceived cognitive impairment in breast cancer survivors

Abstract: Purpose This cross-sectional study was designed to explore potential factors associated with perceived cognitive impairment (PCI) in breast cancer survivors compared to controls and gain insight into perceived levels of severity for cognitive complaints. Methods Women (N=363, 317: breast cancer, 46: healthy controls) completed demographic questionnaire, MD Anderson Symptom Inventory, Attentional Function Index, and Functional Assessment for Cancer Therapy-Cognition. Group classification included pre-chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 47 publications
6
57
1
Order By: Relevance
“…We conducted an exploratory candidate gene substudy participants who took part in a larger cross-sectional parent study [2]. The parent study was designed to investigate potential predictors of perceived cognitive impairment for women with breast cancer and included 363 participants (317 women with breast cancer and 46 controls).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We conducted an exploratory candidate gene substudy participants who took part in a larger cross-sectional parent study [2]. The parent study was designed to investigate potential predictors of perceived cognitive impairment for women with breast cancer and included 363 participants (317 women with breast cancer and 46 controls).…”
Section: Methodsmentioning
confidence: 99%
“…PCF is an individual’s perception of their cognitive ability and is subjectively assessed through patients’ self-report. Our own work demonstrated a negative association between BMI and PCF that was reduced by higher exercise frequency [2]. However, to our knowledge, no studies have been conducted to investigate the relationships between genetic variability for inflammation, behaviorally-related variables (such as BMI and exercise patterns), and PCF for breast cancer survivors.…”
Section: Background/significancementioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary Table 1 lists the potential demographic, clinical, and symptom predictors that were developed based on a review of the literature on factors associated with changes in attentional function and cognitive in oncology patients undergoing CTX (for reviews see 10, 2931). …”
Section: Methodsmentioning
confidence: 99%
“…The AFI was developed by Cimprich and colleagues to evaluate changes in executive function in women undergoing breast cancer surgery [5]. More recently, changes in attentional function were evaluated in patients with breast and prostate cancer undergoing radiation therapy [6,7]; in patients who were followed for 6 months after breast cancer surgery [8]; and in cancer survivors [9,10]. However, no studies were found that evaluated for changes in self-reported attentional function in patients receiving multiple cycles of CTX.…”
Section: Introductionmentioning
confidence: 99%